Reflection on the recognition of marriage between persons of the same sex in the light of the ECtHR Decision in the case of “Buhuceanu and Others v Romania - Chicos, Oana (Acta Universitatis Danubius. Juridica, 2024)
The issue of marriage between persons of the same sex has frequently sparked both emotional and political debates between supporters and opponents, and the debates related to unions concluded between persons of the same sex continue very strongly. Analyzing these aspects, it can be observed that in the Convention for the Defense of Human Rights and Fundamental Freedoms no right is guaranteed regarding marriage between persons of the same sex, but nevertheless, an attempt is made to build a right of legal recognition for couples formed by people of the same sex. The European Court of Human Rights highlighted that it is the right of the member states to protect marriage and the family, this being done with the “specific realities of each state”. In relation to the Romanian legislative framework, we underline the fact that the only form of union accepted by Romanian law is the traditional marriage, which is concluded between men and women. Or, we raise the question, if the Convention for the Protection of Human Rights and Fundamental Freedoms does not guarantee any right regarding same-sex marriage, and the European Court of Human Rights highlights the fact that every state is obliged to protect marriage and the family in relation to the realities and own beliefs, why does the latter force the Romanian state to go over constitutional beliefs and values? In order to be able to make legal arguments on this matter, I believe that we must not give up the fundamental values of a state and force citizens to give up their traditional values and culture. I am of the opinion that before promoting any action, there must be a balance between traditional values and the law, and the legislative framework must be harmonized with the specific realities of each state.